Culture as part of the tourist offer - Case study of the Homeland Museum/Castle of Culture in Vrnjačka Banja - Jelena Borović – Dimić (Mенаџмент у хотелијерству и туризму, 2015)
The aim of this paper is to present the cultural offer through the presentation of our programmes of the Vrnjačka Banja museum as part of Serbian general tourist offer. The programme is designed to provide visitors a high-quality programmes constantly. It is created in collaboration with our renowned cultural heritage institutions, as well as other cultural institutions, artists and foreign embassies and institutes. Described events are dynamic and diverse. The programme in our own production is based on valorising values of Vrnjačka Banja Spa incorporated in its identity. In 2014, in addition to seeing permanent exhibitions, all tourists and citizens could attend 14 galaopenings of other exhibitions, 27 musical evenings, 25 educational programme film evenings and 5 lecture presentations.